Phase diagram for light-induced superconductivity in κ−(ET)2−X - Buzzi, M; Nicoletti, D; Fava, S; Jotzu, G; Miyagawa, K; Kanoda, K; Henderson, A; Siegrist, T; Schlueter, JA; Nam, M-S; Ardavan, A; Cavalleri, A (American Physical Society, 2021)
Resonant optical excitation of certain molecular vibrations in κ−(BEDT−TTF)2Cu[N(CN)2]Br has been shown to induce transient superconductinglike optical properties at temperatures far above equilibrium Tc. Here, we report experiments across the bandwidth-tuned phase diagram of this class of materials, and study the Mott insulator κ−(BEDT−TTF)2Cu[N(CN)2]Cl and the metallic compound κ−(BEDT−TTF)2Cu(NCS)2. We find nonequilibrium photoinduced superconductivity only in κ−(BEDT−TTF)2Cu[N(CN)2]Br, indicating that the proximity to the Mott insulating phase and possibly the presence of preexisting superconducting fluctuations are prerequisites for this effect.